The amendatory proposals of articles 9, 24, 32 of the Constitution recently approved by the Senate - Bompiani, Adriano (Medicina e Morale, 1992)
This paper presents the amendatory proposals of articles 9, 24, 32 of the Constitution recently approved by the Senate. The amendments tend to introduce the concept of "environment" pleno iure in the Constitution, distinguishing it from "landscape". The author concentrates particularly on the following themes: 1) the definition of the widespread interest and of the collective interest; 2) the doctrine of the environment as "widespread interest" and the other hypotheses of classification; 3) wholesome and unwholesome environmental factors.